THEORETICAL FOUNDATIONS OF CLOUD COMPUTING AND THEIR APPLICATION IN ECONOMICS - Бабаева Сабинабону Давронбек қизи (Ecominds Press, 2025)
The article reveals the theoretical foundations of cloud computing, its key characteristics and implementation models. The economic mechanisms of the impact of cloud technologies on business processes, industries and the national economy as a whole are considered. Special attention is paid to the advantages and disadvantages of cloud solutions, as well as examples of practical application in various fields — from the public sector to industry and education implementation and outlines the prospects for the development of cloud computing in the context of the digital transformation of the economy.
Keywords: Cloud computing, digital economy, IaaS, PaaS, SaaS, economic benefits, digitalization, multi-cloud strategies.